Thematic Structure in Scientific Texts (Jurnal Bahasa, 2019)
Scientific texts are rich in unique linguistic features in conveying scientific knowledge, values, and beliefs. One of them is the theme and rheme aspect. Theme plays an important role as a point ofdeparture of a message and each theme selection has its own purpose and is not arbitrarily chosen because what is prioritized will be foregrounded in sentences. The remainder of the message is called rheme, which contains new information to be delivered to readers or listeners. This study is an analysis of the types of theme used in nine research articles from three different disciplines, namely from the pure sciences (ST), social sciences (SS), and humanities (SK). Subsequently, the journal structures were synthesized according to the IMRD model by Swales (1990) and the data were analysed using the Systemic Functional Grammar approach (Halliday & Matthiessen, 2014). The result reveals that the texts of all three disciplines show a preference for marked theme as compared to unmarked Theme. More importantly, this study concluded that the selection of the types of theme is associated with the nature of the discipline and the nature of the rhetorical parts of scientific texts. This research provides a holistic explanation of the thematic structure and a comprehensive understanding of the textual dimension of scientific texts.